Análisis bibliométrico de la literatura sobre fósiles en el Perú, 1840-2020 - Urbizagástegui-Alvarado, Rubén (2021)
Statistical analysis of the literature published on Peruvian fossils up to June 2020. The types of documents published, the languages in which they are published, the authors who publish on this subject, the nucleus of producers, the stratification and concentration of researchers, as well as the dissemination of published literature are analyzed. Univariate statistical measures were used to quantify the types of documents and the languages of publication. The zonal distribution proposed by Bradford's model was used to identify the core of authors, whereas the dissemination of published literature was measured with the Goffman model. There were 680 titles produced by 806 different authors from 1840 to June 2020. The published documents were disseminated as articles in scientific journals and lectures given at national or international congresses, as well as theses, books, book chapters, manuscripts and research reports. The languages of these documents were basically English and Spanish. The division into zones according to the Bradford model identified a group of 5 authors as the nucleus of producers. Regarding the production and continuity of research, 42 authors of the total population ensure the continuity of research in this field. In relation to the researcher concentration index, it was also found that most of the documents are produced by a small number of highly productive authors, which was validated by the Pratt index, the Gini index, and the Lorenz curve. This field entered an accelerated process from the year 2000 onwards.